Studi tentang Motivasi Wisatawan dalam Mengunjungi Kawasan Kuliner Pasar Lama, Tangerang - Ozi Setiawan; Siska Mandalia (Yayasan Literasi Sains Indonesia, 2024)
Gastronomic tourism plays an important role in enhancing the attractiveness of tourist destinations by offering unique and authentic culinary experiences. This study aims to understand the motivations of tourists in choosing Pasar Lama, Tangerang City, as a culinary tourism destination. A qualitative approach with in-depth interviews and direct observation was used in this study. The results showed that the main motivations of tourists were curiosity about typical local food, different culinary experiences, and the opportunity to understand regional culinary culture. The quality of the dishes, menu diversity, and market atmosphere also contributed to tourist satisfaction. However, challenges such as infrastructure, consistency of food quality, and cleanliness still exist. This study provides insights for destination managers and the community to develop Pasar Lama as a sustainable culinary tourism destination, as well as contributing to the preservation of local culture and improving the economy of the local community.